BUILDING BRIDGES ON THE LINEAR TECHNOLOGY CYCLIC SLIDING. THE GERMAN EXPERIENCE - Kanshin, E. (Science and Transport Progress, 2010)
The basic provisions of technology of the cyclic longitudinal pulling down of bridges are presented in the article. The historical review and examples of effective application of technology for building of modern transport structures of complicated configuration in the straitened conditions of performing the work are given.